Factors Related to Compliance with HBsAg Screening Among Pregnant Mothers in Bengkulu Province - Sofais , Danur Azissah Roesliana; Suyanto , Jipri; Rustandi , Handi; Susanty, Sri (Public Health of Indonesia, 2024)
Background:The low number of Hepatitis B surface antigen (HBsAg) screenings indicates that the people of Bengkulu Province have a limited understanding of the importance of such examinations. In Bengkulu, 1.61% of pregnant women, or approximately 47.550 individuals, are positive for hepatitis B infection. This is partly due to the low rate of HBsAg screening among pregnant women. Objective:To determine the prevalence of HBsAg screening compliance among pregnant women and the factors influencing it. Method:This research utilized a cross-sectional study design. A multistage random sampling method was used to select 488 pregnant women from nine districts and one city in Bengkulu Province. Data analysis was performed using multiple logistic regression. Results:The findings showed a non-compliance rate for the HBsAg test of 77.87% (95% CI: 73.95-81.34). Factors associated with non-compliance included maternal perception (adjusted OR: 7.01, 95% CI: 3.62–13.57), quality of life (adjusted OR: 6.19, 95% CI: 2.98–12.88), husband's support (adjusted OR: 2.16, 95% CI: 1.11–4.18), and health worker support (adjusted OR: 3.68, 95% CI: 1.91–7.08). Conclusion:It is crucial for pregnant women to increase their awareness of the importance of HBsAg screening, supported by their husbands, with additional counseling on the negative impacts of hepatitis B during pregnancy. Cultural perceptions should be addressed to foster more positive attitudes. Enhanced collaboration between health service providers, traditional or community leaders, and the public is necessary to improve overall public health outcomes. Keywords: HBsAg screening compliance; health literacy; quality of life; perception; husband support; health worker support